(untitled) (INTERNATIONAL JOURNAL OF RESEARCH IN EDUCATION METHODOLOGY, 2014)
The present study was conducted in order to overcome the problems associated to the unsatisfied assessment literacy needs of the university students with the aid of textbook monitoring procedure. To this end, using the teachers recommendations, the book entitled testing language skills: from theory to practice which is a well-known book being taught at Iranian BA testing courses of English translation and English literature was analyzed from the perspective of assessment literacy and in line with the monitoring and assessment dimension of Nation and Macalisters (2010) framework of curriculum design. This analysis was instantiated with interviews regarding learners assessment literacy expectations of their BA testing courses. Then monitoring was performed based on the identified components that were required for learners and the objectives maintained by the authors in the initial pages of the book.